The distribution of Culex mosquitoes in Coimbatore, Tamil Nadu, India - A. Naresh Kumar; K. Murugan; C. Thomas Vincent; P. Madhiyazhagan; T. Nataraj; K. Shobana (Journal of Entomological and Acarological Research, 2015)
Lymphatic filariasis is an infection with the filarial worms, Wuchereria bancrofti, Brugia malayi and B. timori. These parasites are transmitted to humans through the bite of an infected Culex mosquito and develop into adult worms in the lymphatic vessels, causing severe damage and swelling (lymphoedema). Mosquito control, in view of their medical as well as economical importance, assumes global importance. Geographic information system (GIS) is a powerful tool to analyse the distribution of mosquitoes and their relationship to different environmental factors, and can substantially improve our ability to quantify the impacts of demographic, climatic and ecological changes in vector distribution. In the present study Culex quinquefasciatus, Culex tritaeniorhynchus and Culex gelidus were recorded in the study area. Few other factors such as larval mosquito density, number of breeding sites, human population, etc. were also analysed for its impact on the distribution of Culex mosquitoes. Distribution of Culex in the present study affirmed that C. quinquefasciatus is predominant in the entire focal area, which explains the behavioural response and capability of the species in varied zones. Information gathered from this study is being used to construct a GIS-based mapping system for distribution of Culex mosquitoes in the Coimbatore District, Tamil Nadu, India.